An Empirical Examination of the Form of Relationship Between Sustainable Tourism Experiences and Satisfaction. Issue 7 (2nd July 2016) - Liu, Chih-Hsing; Horng, Jeou-Shyan; Chou, Sheng-Fang; Chen, Ying-Chun; Lin, Yi-Chun; Zhu, Yu-Qian
Abstract : This paper problematizes the terms "sustainable tourism and satisfaction". It conceptualizes sustainable tourism as a future trend in tourism and argues that although sustainable tourism and satisfaction frequently function as a means of tourist evaluation and experience for attractions, their social significance extends far beyond current tourism planning. This paper uses empirical material from 642 tourists who had sustainable tourism experiences and gathers samples from several natural resource conservation zones in Taiwan. If tourists feel a sense of novelty about a tourist destination, they may increase their sustainable experience and further enhance their willingness and satisfaction toward sustainable tourism. In addition, sustainable tourism studies suggest that novelty enhances emotional excitement, which in turn leads to more overall valuable evaluations and higher satisfaction. This paper tests both direct and indirect mechanisms simultaneously using structural equation modeling methods. The results support the predictions.